Spontaneous reaction formation of Cr23C6 diffusion barrier layer between nanocrystalline MCrAlY coating and Ni-base superalloy at high temperature. (October 2015) - Ren, Pan; Zhu, Shenglong; Wang, Fuhui
Highlights: A Cr23 C6 interlayer is spontaneously formed in the nanocrystalline NiCrAlY coating prepared by magnetron sputtering. This Cr23 C6 interlayer exhibited good performance in suppressing the interdiffusion. The Cr23 C6 interlayer showed good thermal fatigue resistance in the thermal shock test. The growth kinetics of the Cr23 C6 interlayer was studied. Abstract: A nanocrystalline NiCrAlYHfSi coating was prepared by magnetron sputtering. The coating after post-annealing comprised matrix γ′-Ni3 Al and α-Cr precipitates. No coating spallation was observed after 100 cycles of 1000–25 °C water-quenching test. A continuous Cr23 C6 interlayer between the coating and the substrate was spontaneously formed during high temperature exposure, and exhibited good performance in suppressing the coating/substrate interdiffusion. The α-Cr precipitates in the coating disappeared gradually as Cr in the coating was consumed to form the Cr23 C6 interlayer. Its growth rates can be fitted into a law controlled by two completing processes: a parabolic growth and a linear decomposition.